Use of Essential Oils for the Prevention of Biofilm Formation on Silicone Rubber High Voltage Insulators. Issue 4 (November 2015) - Atarijabarzadeh, Sevil; Lacamprett, Carla Salas; Karlsson, Sigbritt; Strömberg, Emma
The prevention of biofilm formation on high voltage insulators is important to avoid changes in the surface properties of the material and the subsequent failure of the application. Antimicrobial silicone rubber samples were prepared by the addition of thymol and eugenol to Sylgard 184 to determine the possibility of using natural antimicrobial agents present in essential oils in materials used for high voltage insulators. The antimicrobial effects of thymol and eugenol were studied for different fungal strains and for green algae identified in the biofilms formed on insulators in Tanzania, Sri Lanka and Sweden. It was successfully demonstrated that samples containing high amount of eugenol and different concentrations of thymol could inhibit the fungal growth of strains from Sri Lanka and Tanzania and the growth of green algae. The growth of strains from Sweden was also suppressed. The addition of eugenol to the material resulted in a non-crosslinked system and therefore, the antimicrobial effect of the additive in the material could not be assessed. The addition of thymol did not significantly influence the thermal and mechanical properties of Sylgard184. Although thermal analysis revealed that a large amount of the antimicrobial agent was lost during sample preparation, the materials were effective against microbial growth, even at low thymol concentrations.